Pengaruh Pemberian Jenis Pupuk Kandang Dan Dosis Eco Enzyme Terhadap Pertumbuhan Dan Hasil Tanaman Mentimun Jepang (Cucumis sativus L. Var Roberto) - aisyah izza virahana (AGRONISMA, 2022)
Cucumber plant is one of the annual vines belonging to the Cucurbitaceae family. There are many types of cucumbers, one of which is the Japanese cucumber (Cucumis sativus L. Var Roberto). This type of cucumber has several advantages, including: longer size, slender fruit shape, soft flesh, greener skin color, sweeter taste, crunchier, and less water content. This study aims to determine the effect of giving the right type of manure and eco-enzyme dose on the growth and yield of Japanese cucumber plants. The method used is a factorial RAK which consists of two factors. The first factor is the type of manure consisting of three levels (cow, goat, and chicken). The second factor is the dose of eco enzyme consisting of three levels (6.57 ml, 13.14 ml, and 19.17 ml). The results showed that the P2E1 treatment combination produced good fruit weight per hectare with an average of 27.09 tons ha-1, but it was not significantly different from the P1E1 treatment combination with an average of 23.59 tons ha-1.Keywords: Japanese cucumber, cow, goat, and chicken manure, eco enzyme dose